Crossing the Moral Threshold: A Longitudinal Examination of Internet Addiction and Adolescent Cyberbullying. - Xie, Kexin; Li, Chunkai (Child & Family Social Work, 2026)
Previous studies have suggested links between internet addiction and cyberbullying among adolescents, whereas the underlying psychological mechanisms remain unclear. In particular, the mediating role of internet morality and the distinct pathways associated with different types of internet addiction have received limited empirical attention. Besides, gender differences in these relationships remain inconsistent, and few studies have used longitudinal data to validate the mechanisms. Therefore, this study aimed to explore whether internet morality mediates the associations between game addiction, social media addiction and cyberbullying, and whether these pathways vary by gender. A two‐wave panel survey was conducted over a 6‐month interval with 629 adolescents from China, and a half‐longitudinal mediation model was employed to test the hypothesized relationships. Results showed that both game addiction and social media addiction negatively predicted internet morality (β = −0.171, p < 0.001; β = −0.147, p < 0.01), which in turn negatively predicted cyberbullying (β = −0.174, p < 0.01). Internet morality significantly mediated the relationship between game addiction and cyberbullying (Z = 1.970, p < 0.05), but not between social media addiction and cyberbullying (Z = 1.463, p > 0.05). Finally, game addiction significantly predicted lower internet morality among males but not among females, while social media addiction was significantly associated with lower internet morality among females but not males. These findings provided empirical support for the cognitive mechanisms through which internet addiction contributes to cyberbullying, highlighted the protective role of internet morality and revealed gender‐specific patterns. Promoting internet morality through digital literacy and moral education may serve as an effective strategy to reduce cyberbullying among adolescents.